Research on Central America and Caribbean education in the Handbook of Latin-American Studies 1969-1981 - Eggington, Everett
This study analysed the abstracts of the publications on Central American and Caribbean education reviewed in the "Handbook of Latin American Studies" since 1969. The abstracts in every education section of the Handbook since 1969 were carefully examined and classified according to a coding system devised by the author. In addition, the study analysed the reviewers' critical assessments of the publications, compared the publications on South America with those on Central America and the Caribbean, and compared the publications on education in Central America with those related to education in the Caribbean
Keywords: Educational research